Relocation potentiates obesity and cardiovascular risk: A case–control study on relocatees from the Three Gorges area: 重新安置可导致肥胖与心血管的风险增加:一项来自三峡地区移民的病例对照研究. (12th July 2016) - Huang, Hantao; Peng, Miaomiao; Zhang, Jiaoyue; Hu, Xiang; Chen, Lulu
Abstract : Highlights Relocatees of The Three Gorges, compared with original inhabitants, are at higher risk of general and abdominal obesity, and other metabolic disorders associated with cardiovascular risk, such as insulin resistance, dyslipidemia, and metabolic syndrome. The process of rapid nutritional transition from under‐nutrition to subsequent nutritional restoration in adulthood, which is associated with the relocation, may be one of the major factors for the metabolic disorder epidemic in Asia.